(untitled) (Docentes 2.0 Journal, 2025)
Teachers’ digital competence is a continuous learning process in which they model, practice, and perfect their technological skills. This study aimed to analyze the self-perception of Peruvian teachers in regular basic education regarding the digital competence they implement in their teaching process with students, according to their dimensions, gender, area of specialization, and type of educational institution. A research study was conducted within the positivist paradigm, using the hypothetical-deductive method, a quantitative approach, and a non-experimental, descriptive, and cross-sectional design, with a sample of 157 teachers. The survey technique was employed to collect data, using a questionnaire to assess teachers’ self-perception of their mastery of digital competencies. The main results show that teachers have achieved consolidation of advanced digital competencies; however, there are also percentages at an intermediate level in the dimensions due to gaps in information and communication technologies. Likewise, there is no evidence of a significant difference in digital competencies between teachers based on gender, or between those working in urban and rural areas, and in public and private institutions. It is concluded that teachers can effectively carry out their teaching tasks by efficiently developing digital skills, integrating them into the pedagogical process with a reflective and self-critical attitude, and a commitment to continually developing digital literacy to foster meaningful learning in students.